PENGEMBANGAN MODUL PEMBELAJARAN TRAINER KIT ARDUINO BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PEMROGRAMAN MIKROKONTROLER DAN ALGORITMA DI SMKN 1 SIDOARJO - Ryan Rasidi Purwanto; L. Endah Cahya Ningrum; Fendi Achmad; Yulia Fransisca (Jurnal Pendidikan Teknik Elektro, 2027)
The problems identified in this study include the limited availability of practicum media and teacher-centered learning, which results in students being less active and having difficulty understanding programming concepts in an applied manner. These limitations are found in subjects that focus on analog systems, causing students of Grade XI Audio and Video Engineering at SMKN 1 Sidoarjo to struggle to understand Microcontroller Programming and Algorithms. This study aims to develop a module and Arduino trainer kit learning media based on Project-Based Learning to improve students’ learning outcomes in the Microcontroller Programming and Algorithms course. The research employed a Research and Development (R&D) method, along with the Shapiro-Wilk test, focusing on media development and comparison between two classes. The research instruments consisted of expert validation sheets, student response questionnaires, and learning outcome tests. The data were analyzed using quantitative descriptive techniques, normality testing, t-test, and N-Gain calculation. The results showed that the validation score of the teaching module was 94%, the student worksheet was 98%, and the questionnaire was 99%, indicating that the developed module is categorized as highly valid. The practicality level reached 81%, categorized as very practical. The effectiveness test results showed an improvement in students’ learning outcomes after the implementation of the Project-Based Learning module. Based on these findings, the developed learning module is feasible and effective in improving the learning outcomes of Grade XI TAV students. Keywords: learning module, Arduino trainer kit, project based learning, learning outcomes.